2014
DOI: 10.1103/physrevb.89.220509
|View full text |Cite
|
Sign up to set email alerts
|

Upper critical field ofKFe2As2under pressure: A test for the change in the superconducting gap structure

Abstract: We report measurements of electrical resistivity under pressure to 5.8 GPa, magnetization to 6.7 GPa, and ac susceptibility to 7.1 GPa in KFe2As2. The previously reported change of slope in the pressure dependence of the superconducting transition temperature Tc(p) at a pressure p * ∼ 1.8 GPa is confirmed, and Tc(p) is found to be nearly constant above p * up to 7.1 GPa. The T -p phase diagram is very sensitive to the pressure conditions as a consequence of the anisotropic uniaxial pressure dependence of Tc. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
62
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 66 publications
8
62
4
Order By: Relevance
“…We show that the slope of H c2 (T ) jumps by a factor 2 across P c , in a manner that also appears to be universal. This is compelling evidence for a sudden change in the gap structure, 8 which we attribute to a change of pairing symmetry. The Fermi surface of KFe 2 As 2 is known in detail from quantum oscillations studies.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…We show that the slope of H c2 (T ) jumps by a factor 2 across P c , in a manner that also appears to be universal. This is compelling evidence for a sudden change in the gap structure, 8 which we attribute to a change of pairing symmetry. The Fermi surface of KFe 2 As 2 is known in detail from quantum oscillations studies.…”
Section: Introductionmentioning
confidence: 89%
“…5,6 Our results on KFe 2 As 2 have been reproduced by other groups. [7][8][9] We interpreted the transition at P c as a change of pairing state, possibly from d to s ± , where the decreasing T c of the former meets the growing T c of the latter at P c , resulting in a V-shaped phase diagram.…”
Section: Introductionmentioning
confidence: 99%
“…The value of the critical pressure is nearly independent of the amount of the disorder in K-122 but it is reduced in the unsubstituted clean Cs-122 21 . However, V. Taufour et al, showed that the pressure dependence of T c for K-122 is sensitive to the pressure medium 19 , and that for the best pressure (hydrostatic) conditions the reversal behavior of T c is replaced by a broad minimum followed by a nearly pressure independent T c value above 2.5 GPa. From the almost pressure independent behavior of the Hall coefficient extrapolated to T = 0 as well as from the residual resistivity, it was concluded that the topology of the Fermi surface does not change across the critical pressure.…”
Section: Introductionmentioning
confidence: 99%
“…21 Alternatively, V. Taufour et al proposed that a change of symmetry under pressure may not occur at all. 19 These authors empirically supposed that the critical pressure could be a consequence of anisotropic pressure derivatives, since the pressure derivatives along the a axis and the c axis are negative and positive, respectively. In this case, the critical pressure corresponds to the critical pressure in the ab plane above which the slope of T c (P ) depends on the value of ∂T c /∂P c > 0, only, whereas ∂T c /∂P ab ≡ 0 for P ≥ 2 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement (rather than suppression) of T c in SC1 can be possibly explained by the reduction in hydrostatic pressure conditions produced by the steatite powder in our DAC experiment, as compared to the previous clamp-cell experiments. While the level of hydrostaticity at low pressures is generally con- sidered good in this configuration, the sensitivity of T c in KFe 2 As 2 to uniaxial components may be susceptible to such differences and may explain the variation of T c values reported at low pressures [12,13,[16][17][18]. We can estimate the slope of T c as a function of uniaxial pressure by using the thermodynamic relation for the second-order transition, or the Ehrenfest relation [25,26],…”
mentioning
confidence: 99%